-9-6=8+x

Simple and best practice solution for -9-6=8+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9-6=8+x equation:


Simplifying
-9 + -6 = 8 + x

Combine like terms: -9 + -6 = -15
-15 = 8 + x

Solving
-15 = 8 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-15 + -1x = 8 + x + -1x

Combine like terms: x + -1x = 0
-15 + -1x = 8 + 0
-15 + -1x = 8

Add '15' to each side of the equation.
-15 + 15 + -1x = 8 + 15

Combine like terms: -15 + 15 = 0
0 + -1x = 8 + 15
-1x = 8 + 15

Combine like terms: 8 + 15 = 23
-1x = 23

Divide each side by '-1'.
x = -23

Simplifying
x = -23

See similar equations:

| (y^2-7)(5y^2-5y+6)= | | 2+38= | | -13=7p-12-6p | | 36r^9-9r^6+54r^3= | | 7(3x-4)=17x | | x+6/5+x-1/4=2 | | 11=8p-14-7p | | n^2=4n+5 | | 1/2y-1/3x-1=0 | | -3=3p+11-2p | | 6=-6p-10+7p | | a+3ab-4ab= | | 3x-5+9x=-15 | | 8x^3-49x^2+6x=0 | | -8+10=9x+17 | | 1+a+x^2=p | | -9=-6p-7+7p | | y-4=(x-7)(x-7) | | 3=-4.5+4y | | -9=5p-12-4p | | x+19=139 | | 22x=-12 | | 2=-4.5+4y | | -16=-5(8n+3) | | -6=-9p+14+10p | | 1=-4.5+4y | | 121b^2-100= | | 0=-4.5+4y | | 2x-19=1421 | | 27=6+8+c | | 10x+20/25x+20 | | 191=-3x+7(4x-12) |

Equations solver categories